Georgia : Towards Green and Resilient Growth - World Bank (World Bank, Washington, DC, 2020)
Georgia has made remarkable progress in terms of economic growth and poverty alleviation. In 2019, the country became an upper middle-income country Georgia’s endowment of natural resources is a significant source of national wealth and has the potential for accelerating inclusive socio-economic development. Yet, challenges persist as poverty and inequality remain high, especially in rural areas. The Coronavirus (COVID-19) induced global recession has affected important sectors of the economy, including tourism and the travel industry. This report fills knowledge gaps in the upstream importance of environment and natural assets, and highlights areas for aligning national strategies with sustainable recovery from the Coronavirus (COVID-19) pandemic. In so doing, the report aims to inform national policies by which Georgia has commitments to “greening” sector developments aligned with the provisions of the EU–Georgia Association Agreement. The analysis underlying the report includes updates to the cost of environmental degradation (CoED) published in 2015. It also reflects the new government priorities and options for addressing specific challenges in forest management, land and coastal degradation, and air pollution. The recommendations of this report are designed for a wider audience, including the government of Georgia, as well as development partners and broader society.